The IMPACT OF FLASH SALES AND DISCOUNT PROGRAMS ON IMPULSIVE BUYING: THE MEDIATING ROLE OF POSITIVE EMOTIONS IN SHOPEE’S MARKETPLACE IN JAMBI - Yuliarnita; Syahmardi Yacob; Tona Aurora Lubis (Journal of Business Studies and Management Review, 2025)
This study aims to examine the influence of flash sales and discount programs on impulsive buying, with positive emotions as a mediating variable, in the Shopee marketplace in Jambi. A quantitative approach was employed, with data collected through questionnaires distributed to 96 Shopee users in Jambi. The data were analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. The results indicate that the flash sale program does not have a significant effect on impulsive buying or positive emotions. In contrast, discount programs significantly influence both impulsive buying and positive emotions. Additionally, positive emotions have a significant impact on impulsive buying. While flash sales do not indirectly affect impulsive buying through positive emotions, discount programs do. These findings suggest that discount-based promotional strategies are more effective in driving impulsive purchases than flash sales. This study provides valuable insights for e-commerce businesses in designing more effective marketing strategies to enhance consumer engagement and sales performance. Keywords: Flash Sale, discount, impulsive buying, positive emotions, marketplace Shopee.